HAMBATAN SISWA DALAM BELAJAR MATEMATIKA DIKAJI DARI KEPERCAYAAN MATEMATIS - Armiyansyah Armiyansyah; Sugiatno Sugiatno; Bistari Bistari (UNIVERSITAS TANJUNGPURA, 2021)
The purpose of this study was to find out the learning obstacles in linear program assessed by mathematical beliefs at the Mujahidin Senior High School. The form of research used in this study is a case study. The data source used in this study was the students of class XI MIPA 1 in Pontianak Mujahidin High School, the data of which were the results of students' mathematical belief questionnaires and the answers of research subjects on the given test. Students learning obstacles in linear program material revealed in this study were assessed from mathematical beliefs including: students with mathematical beliefs in believing about mathematical characteristics have obstacles in the form of not being able to determine the mathematical model of linear program because he not understand teacher explanations, students with mathematical belief in believing about self abilitiy have an obstacles like not being able to mention the benefits of a linear program, students with mathematical beliefs in believing about teaching mathematics experience obstacles like not being able to make mathematical models correctly and the last is students with mathematical beliefs in believing about the usefulness of mathematics experiencing obstacles like not being able to make mathematical models because forget..